The History of Human Rights Politics - Siswadi, Imran; Supriadi, Supriadi (UNISKA LAW REVIEW, 2023)
The authors want to look at how human rights politics in the history of human rights development (19th Century and The First Decade of the 20th Century) has changed in the past and now. The authors try to anlayse, investigate, and explain the basic structure and political position backgrounds of the human rights in the historical development. In the study of normative law, it tries to investigate, explain, and analyze the basic structures and political positions of the rights of the people. Then, normative juridical method is applied for this study. The results show that the power relationship among contries and conflicting alliance patterns has experienced a shifting of basic structure in the previous and now, and the power relations among contry patterns have experienced the shift of basic structures.